Kebijakan Regulasi Dan Praktik Terkini Dalam Perlindungan Hak Kekayaan Intelektual di Indonesia - Rahmalia Rahmalia; Delfiana Sundari (Pusat Riset dan Inovasi Nasional, 2024)
This journal investigates current regulatory policies and practices relating to the protection of intellectual property rights (IPR) in Indonesia. By focusing on the existing legal framework and the latest developments in the implementation of IPR policies, this research reveals the challenges and opportunities that Indonesia faces in safeguarding its intellectual property in the era of globalization and digitalization. Through a case study approach and literary insights, this journal also explores the impact of policy and innovation on the country's innovation, creativity and economic growth. The findings from this research provide valuable insights for policy makers, legal practitioners and industry players in strengthening the IPR protection system in Indonesia to support sustainable and inclusive economic development.